Chronic Pain, Dietary Intake and Exercise Behaviors in a Nationally Representative Sample of US Adults. (7th June 2021) - Vernarelli, Jacqueline; MacLean, R Ross
Abstract: Objectives: An estimated 50 million adults in the US have chronic pain, and is one of the most cited reasons for seeking medical treatment. There are well-established associations between dietary patterns, nutrient intake, and musculoskeletal health. Dietary habits can influence inflammation and inflammatory markers, both of which can contribute to chronic pain, however few studies have examined the association between dietary intake patterns and chronic pain. The present study examines the relationship between chronic pain and dietary behaviors in a nationally representative sample of US adults. Methods: Pain assessment was conducted during only one cycle of NHANES (2009–2010). During the examination visit, participants between 20–69 years were asked questions related to pain location and duration. Individuals with chronic pain were identified as those who reported current pain in the back or neck, with a history of pain lasting almost every day for at least 3 months ( n = 794). Physical activity data was categorized as 'moderate' or 'vigorous' activity in the NHANES dataset, and reported as daily minutes; minuets of sedentary behaviors was also reported. Dietary data was collected using 24hour-recall. All data were analyzed using SAS 9.4 survey procedures to account for the complex survey design of the NHANES. Results: Chronic pain was not associated with differences in amount of time engaged in moderate or sedentary activities. Chronic pain was associated with multiple differences in dietary intake compared to a representative sample of US adults. Differences were noted in macro- and micronutrient intake, as well as dietary pattern differences. Individuals with chronic pain reported higher intakes of total fat and added sugars ( P = 0.003); and lower intakes whole grains and fiber ( P = 0.01), and were found to consume 32% less fruit ( P = 0.05) resulting in lower intake of beta-carotene (∼1700 vs 2100 mcg, P = 0.01). Though chronic pain was associated with higher overall fat intake, no difference in intakes mono- and polyunsaturated fats were observed. Conclusions: This study supports prior research demonstrating that chronic pain is associated with dietary patterns that are higher in total fat and sugar, and lower in fiber and micronutrients. Additional research is needed to evaluate whether dietary interventions can improve chronic pain status. Funding Sources: None.